Failure analysis of cartridge brass shell. (August 2022) - Yaqoob, Khurram; Hashmi, Fahim; Hassan Tanveer, Waqas
Highlights: A 130 mm shell made up of cartridge brass was reported to crack during firing. These cracks led to shell expansion, which was stuck in the cannon and caused clogging. Microstructural and mechanical characterization of the failed brass shell revealed presence of elongated grains, mechanical twins, relatively higher strength and lower ductility, which pointed out towards the possibility of insufficient annealing times. Discoloration of the crack surface, porous and zinc depleted microstructure near cracks and transgranular mode of failure without multiple branching revealed that the brass shell suffered from plug type dezincification. Reduced strength of the studied brass shell due to dezincification helped in crack initiation whereas reduced ductility due to insufficient annealing time facilitated crack propagation. Abstract: Cartridge brass, because of its high ductility and formability, is used for the development of different ammunition components, plumbing accessories, fasteners, radiator cones etc. A series of cupping, annealing, deep-drawing, tapering and washing operations on the as-received brass disc are generally required for fabrication of different ammunition components. A 130 mm shell made up of cartridge brass was reported to crack during firing. These cracks led to shell expansion, which was stuck in the cannon and caused clogging. Failure analysis of brass shell was carried out. Overall composition of the brass shell was in accordance with 70/30 brass. Microstructural and mechanical characterization of the failed brass shell revealed presence of elongated grains, mechanical twins, relatively higher strength and lower ductility, which pointed out towards the possibility of insufficient annealing times. On the other hand, discoloration of the crack surface, porous and zinc depleted microstructure near cracks and transgranular mode of failure without multiple branching revealed that the brass shell suffered from plug type dezincification. Reduced strength of the studied brass shell due to dezincification helped in crack initiation whereas reduced ductility due to insufficient annealing time facilitated crack propagation. Use of alloys which are more resistant to dezincification as a starting material and optimization of annealing times to obtain desired levels of ductility, were recommended as corrective measures.